Niveles de cargas ganaderas en la dehesa extremeña - Escribano, M.; Rodríguez de Ledesma, A.; Mesías, F. J.; Pulido, F. (Archivos de zootecnia, 2002)
This work analyzes the data collected from 143 sheep and/or cattle farms, representatives of the Extremaduran dehesa (semiarid grazing areas of the SW of Spain). A random survey was carried out in 2000, with an error of less than 5 percent and a confidence level of 95 percent. The aim of the survey was the evaluation of the stocking rate levels of these farms in 1999 and their evolution from 1993, first year after the CAP Reform of 1992. The effects of farm size for different stocking rates are studied. Significant differences were observed (p<0,05 and p<0,01) between the bigger and the lesser farm sizes. This shows a higher productive intensification when the grazing surface decreases. It is to mention a high correlation between the cattle units in sheep farms (UGMo) and the cattle units in the whole sample (UGMt) (r=0,867; p<0,01), as well as the association between sheep density and pig density variables (r=0,773; p<0,01). On the other hand, we can observe an inverse correlation between the levels of livestock density and the farm size, which is more significant in cattle farms.
Keywords: dehesas; Grazing; Stocking rate; Structural analysis